Human T-cell leukaemia virus type 1 and Adult T-cell leukaemia/lymphoma in Queensland, Australia: a retrospective cross-sectional study. (6th May 2022) - Martin, Fabiola; Gilks, Charles F; Gibb, Robert; Jenkins, Alana; Protani, Melinda; Francis, Fleur; Redmond, Andrew M; Neilsen, Graham; Mudge, David; Wolley, Martin; Binotto, Enzo; Norton, Robert; et al.
Abstract : Objectives: Human T-cell leukaemia virus type 1 (HTLV-1), an STI, is reported to be highly prevalent in Indigenous communities in Central Australia. HTLV-1 is an incurable, chronic infection which can cause Adult T-cell leukaemia/lymphoma (ATL). ATL is associated with high morbidity and mortality, with limited treatment options. We studied the prevalence of HTLV-1 and ATL in the state of Queensland, Australia. Methods: Serum samples stored at healthcare services in Brisbane, Townsville and Cairns and at haemodialysis units in Brisbane (2018–2019) were screened for HTLV-1/2 antibodies using the Abbott ARCHITECT chemiluminescent microparticle immunoassay (CMIA) for antibodies against gp46-I, gp46-II and GD21 (Abbott CMIA, ARCHITECT). Reactive samples were confirmed through Western blot. Pooled Australian National Cancer Registry surveillance data reporting on cases coded for ATL (2004–2015) were analysed. Results: Two out of 2000 hospital and health services samples were confirmed HTLV-1-positive (0.1%, 95% CI 0.02% to 0.4%), both in older women, one Indigenous and one non-Indigenous. All 540 haemodialysis samples tested negative for HTLV. All samples were HTLV-2-negative. Ten out of 42 (24.8%) reported cases of ATL in Australia were from Queensland (crude incidence rate 0.025/100 000; 95% CI 0.011 to 0.045); most cases were seen in adult men of non-Indigenous origin. Nineteen deaths due to ATL were recorded in Australia. Conclusion: We confirm that HTLV-1 and ATL were detected in Queensland in Indigenous and non-Indigenous people. These results highlight the need for HTLV-1 prevalence studies in populations at risk of STIs to allow the implementation of focused public health sexual and mother-to-child transmission prevention strategies.